Unlocking inclusive internationalization with public collaborative TNE: binational universities in Vietnam - JungHyun Ryu (Journal of Contemporary East Asia Studies, 2024)
In an era of globalization, the imperative for internationalization in higher education (IHE) is undeniable. However, questions regarding inclusivity and equitable access for students, universities, and nations have prompted the emergence of concepts like inclusive internationalization, or internationalization for all. This article examines how inclusive internationalization can be advanced through collaborative transnational education (TNE), specifically focusing on three binational universities in Vietnam. Through an analysis of their institutional frameworks, curricula, and activities, it explores their contributions to inclusion and equity in IHE. The findings highlight that these universities provide high-quality, internationally accredited programs, effectively leveraging bilateral partnerships. Unlike prevailing neoliberal models in international higher education that often exacerbate disparities, binational universities, as public institutions, address issues of equity in access and social inclusion more effectively. Additionally, their multisector partnerships foster diverse activities, promoting democratic and inclusive participation. This article argues that public collaborative TNE, exemplified by binational universities, supports inclusive internationalization by prioritizing equity and collaboration over prestige and revenue generation. However, challenges such as sustainable financing and faculty recruitment remain significant barriers. Addressing these challenges is crucial to fully realizing the potential of inclusive internationalization and ensuring its benefits are accessible to all stakeholders.